Evaluation of a Trivalent Chromium Process (TCP) Conversion Coating on AA2024-T3 That Requires No Surface Pretreatment. Issue 15 (18th November 2019) - Walton, Jack; Shruthi, T. K.; Yancey, David; Vlasak, Paul; Westre, Sjon; Swain, Greg M.
Abstract : We report on the study of a new commercial trivalent chromium process (TCP) conversion coating, TCP-1, that requires no deoxidation or etching surface preparation of the aluminum alloy for optimum performance. The corrosion resistance provided by TCP-1 and a comparable conversion coating, TCP-2, both formed by immersion on AA2024-T3, were evaluated using scanning electron microscopy and energy dispersive X-ray analysis, digital microscopy, XPS depth profiling, electrochemical impedance spectroscopy and potentiodynamic polarization techniques. Accelerated degradation testing was also performed to determine how the laboratory electrochemical data correlate with the coating's corrosion protection during neutral salt-spray exposure and full-immersion testing. The results indicate that TCP-1 produces a protective coating on the metal that minimizes corrosion to an equivalent degree as TCP-2; a conversion coating that requires a conventional deoxidation step prior to application. Electrochemical data revealed that both TCP coatings increase the polarization resistance by ∼100x and suppress anodic and cathodic currents by ∼10–100x, as compared to the uncoated alloy. Specimens coated with either TCP coating exhibited little degradation, discoloration or corrosion during a 14-day neutral salt-spray (ASTM B117) exposure and a 14-day full immersion in 3.5 wt.% NaCl at 55°C. In summary, the stand-alone corrosion protection provided by TCP-1 to this alloy is as good as the protection provided by a standard TCP coating.